The Effect of Different Feed Restriction Programs and Dietary L-Carnitine Supplementation on Reproductive Performance, Efficiency, Frame Size and Uniformity in Broiler Breeder Hens - Beer, M. de; Coon, C.N. (International Journal of Poultry Science, 2009)
Two experiments were conducted to determine the effect of Everyday (ED) or Skip-a-day (SK) feed restriction programs and L-carnitine supplementation on breeder reproductive performance. In Experiment 1 a 2 x 2 factorial design was used to compare feeding regimens (ED vs. SK) and L-carnitine supplementation (0 vs 50 mg /kg). L-carnitine supplementation began at day 1 and lasted throughout the 45 week experimental period. SK feeding programs were implemented from 28 days of age to 5% production. Feed allocation was adjusted to ensure equal BW between groups. At 21 weeks, 60 pullets from each treatment combination were housed individually. Feeding ED improved the feed conversion ratio by 0.24 units for 21 week pullets, resulted in 3 days earlier attainment of Sexual Maturity (SM), produced 4.6 more total eggs and 5.0 more settable eggs than SK fed pullets. Uniformity was less for ED fed pullets (2.07 higher CV). Egg size was increased by 1.16g with dietary L-carnitine. Body composition was not affected by either feeding regimen or L-carnitine. In Experiment 2, the same effects were tested but a low density grower diet was used from 4-18 weeks. L-carnitine was supplemented from day 1 and SK programs began at day 28 and extended to 5% production. Feed allocation was adjusted to maintain equal BW and 80 pullets per treatment were individually housed at 21 weeks. L-carnitine and ED feeding through 21 wk improved the FCR by 0.06 and 0.12 units, respectively. Feeding ED resulted in 5.8 days earlier SM, 4.7 more total eggs and 4.4 more settable eggs than SK. Uniformity was not affected by feeding regimen or L-carnitine. Carcass fat was reduced and carcass ash was increased by L-carnitine supplementation at 22 weeks. It was concluded that ED fed breeders are more productive than SK fed breeders primarily because of earlier SM. ED fed breeders are more efficient than SK breeder pullets because there are less nutrients wasted for tissue replenishment. Feeding breeder pullets ED with low energy density diets helped eliminate uniformity differences for pullets fed ED and SK feeding regimens. Breeders fed L-carnitine during 21 wk rearing period improved the FCR by 0.06 units for both Experiment 1 and 2. While, the effect of L-carnitine on total egg production was not significant, L-carnitine supplemented birds produced 3.9 and 2.7 more total eggs at 45 weeks than non-supplemented birds in Experiments 1 and 2 respectively. The consistency of the results and the associated p-values (p = 0.12; p = 0.13) for total egg production in the two experiments suggest that L-carnitine may have some beneficial effects on egg production. Breeders fed carnitine also showed significant increases in EW in Experiment 1 and near significant (p = 0.13) increases in EW for the second experiment. Carnitine was unable to attenuate the negative effects of SK feeding associated with the lengthy fasting periods.